Apical adaptation, sealing ability and push-out bond strength of five root-end filling materials - Pablo Andrés AMOROSO-SILVA; Marina Angélica MARCIANO; Bruno Martini GUIMARÃES; Marco Antonio Hungaro DUARTE; Ana Flavia SANSON; Ivaldo Gomes de MORAES (Sociedade Brasileira de Pesquisa Odontológica, 2014)
This study compared the fluid filtration, adaptation to the root canal walls, and the push-out bond strength of two resin-based sealers and three calcium silicate-based retrograde filling materials. Fifty maxillary canines were shaped using manual instruments and the apical portion was sectioned. Retrograde cavities of 3-mm depth were prepared. The specimens were divided into five groups (n = 10): Sealer 26 (S26); MBPc (experimental); MTA; Portland cement with 20% zirconium oxide (PC/ZO), and Portland cement with 20% calcium tungstate (PC/CT). The fluid filtration was measured at 7 and 15 days. To evaluate the interfacial adaptation, sections of the teeth, 1 and 2 mm from the apex, were prepared and the percentage of gaps was calculated. The push-out bond strength at 2 mm from the apex was evaluated. Statistical analysis was performed using the ANOVA/Tukey's test (p < 0.05). At 7 and 15 days (p = 0.0048, p = 0.006), the PC/CT group showed higher fluid filtration values when compared to other groups. At 1 mm from the apex, no statistical differences in the adaptation were found among the cements (p = 0.44). At 2 mm from the apex, the PC/ZO group presented statistically lower percentage of gaps than S26, MBPc, and MTA (p = 0.0007). The MBPc group showed higher push-out bond strength than other cements evaluated (p = 0.0008). The fluid filtration and interfacial adaptation of the calcium silicate-based cements were similar to those of the resin-based cements. The resinous cement MBPc showed superior push-out bond strength.